2011
DOI: 10.4315/0362-028x.jfp-10-364
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Growth of Clostridium perfringens in Commercial No-Nitrate-or-Nitrite-Added (Natural and Organic) Frankfurters, Hams, and Bacon

Abstract: The popularity of "preservative-free" foods among consumers has stimulated rapid growth of processed meats manufactured without sodium nitrite. The objective of this study was to quantify the potential for Clostridium perfringens growth in commercially available processed meats manufactured without the direct addition of nitrite or nitrate. Commercial brands of naturally cured, no-nitrate-or-nitrite-added frankfurters (10 samples), hams (7 samples), and bacon (9 samples) were obtained from retail stores and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 11 publications
3
28
0
Order By: Relevance
“…Bacon had the greatest variability in measured traits partially due, in no small part, to inherent differences in fat and lean content within and between bellies. All product codes assigned to brands in this survey match those used by Jackson et al (2011) in the C. perfringens pathogen challenge study.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Bacon had the greatest variability in measured traits partially due, in no small part, to inherent differences in fat and lean content within and between bellies. All product codes assigned to brands in this survey match those used by Jackson et al (2011) in the C. perfringens pathogen challenge study.…”
Section: Resultsmentioning
confidence: 98%
“…Two replicates were conducted. More specific information on the bacterial challenge studies and the results of these studies can be found in Jackson, Sullivan, Kulchaiyawat, Sebranek, andDickson (2011) for C. perfringens andSchrader (2010) for L. monocytogenes.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%
“…51,52 Naturally cured products have cured meat characteristics similar to conventionally cured meats, 18 but the naturally cured products have less pathogen controls. 19,20 While the amount of ingoing nitrite affects the extent of nitrosation/nitrosylation reaction product formation, the natural curing process does not appear to result in a significant shift of nitrite reaction products. This would suggest that it is more important to increase the amount of ingoing nitrite in naturally cured products than increase the rate of nitrite formation from nitrate.…”
Section: ■ Resultsmentioning
confidence: 99%
“…13−16 However, by utilizing natural nitrate sources, primarily celery juice/powder, and a nitrate-reducing starter culture, nitrite can be formed in natural and organic processed meats and will produce characteristics similar to conventionally cured products that are produced with direct addition of sodium nitrite. 17,18 While these naturally cured products look and taste like traditionally cured meats, Jackson et al 19 and Schrader 20 found increased risk for the growth of Clostridium perf ringens and Listeria monocytogenes, respectively. Many factors can impact pathogen growth in cured meats, but it is likely related at least in part to the curing process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nitrite affects the germination and outgrowth of C. perfringens spores in different types of meat products, and it has been reported that conventionally cured meat products, which have nitrite supplements, showed inhibition of the growth of C. perfringens (29,30). However, commercially available organic meat products have the potential to support growth of C. perfringens (31,32). Although nitrite is a very good antimicrobial agent, unfortunately its use in food products is limited due to its ability to form carcinogenic derivatives (33).…”
Section: Chemical Agentsmentioning
confidence: 99%